Inner Prison of the NKGB (MGB, KGB) of Lithuanian Soviet Socialist Republic 1944–1959 - Indrišionis, Darius (Genocidas ir rezistencija, 2017)
This study discloses the 1944-1959 period history of the inner prison of NKGB (Narodny Komissariat Gosudarstvennoy bezopasnosti, English translation – The People‘s Commissariat for State Security) of Lithuanian Soviet Socialist Republic, including MGB (Ministerstvo Gosudarstvennoy Bezopasnosti, English translation – the Ministry for State Security) and KGB (Komitet Gosudarstvennoy Bezopasnosti, English translation – Committee for State Security) as users of this prison. The significance of this prison in the common system of prisons under State Security Institutions is analysed as well as the cases of collaboration with the prisons operating under Ministry of Internal Affairs. Inner prison routine is analysed: living conditions of prisoners, regime, etc. Direct links between the work of the Interrogation Division of the NKGB (MGB, KGB) of Lithuanian Soviet Socialist Republic and inner prison are disclosed, as well as the procedure of execution at the inner prison. The inner prison was the most important prison of the Soviet secret police organization (Cheka) in Lithuanian Soviet Socialist Republic – political prisoners of special importance were imprisoned there and interrogated in the Interrogation Division located in the same building.In the first post-war years, the inner prison was overcrowded, and prison conditions were poor. They improved just at the end of the fifth decade, because the number of imprisoned persons decreased, and bunks were installed in the cells.In the first post-war decade, during interrogation sessions, employees at the Interrogation Division used to apply not only psychological violence against prisoners, but physical violence as well. In 1953, officially, physical torture measures were prohibited, still cases of physical torturing of prisoners happened even much later.In the period 1944–1969, death sentences were carried out in the inner prison. Over one quarter of the last century, 1 019 persons were executed. Although an official method of carrying out the capital punishment used to be squad firing, the investigation of remains of those executed and buried in the burial grounds in Tuskulėnai, show that people who had been sentenced to death penalty, sometimes, during first post-war years at least, were just tortured to death.
Keywords: Lithuania; Soviet occupation; repressive structures; repressions